Seismic performance of flat slab shear wall system - Garg, C. S.; Singh, Yogendra; Bhargava, Pradeep; Sharma, Umesh Kumar; Bhandari, N. M. (Journal of Structural Engineering, 2025)
Flat slab system is being adopted in many buildings presently due to the advantage of reduced floor heights to meet the economical and architectural demands. Analysis and design of flat slab for gravity loads is well established. But it is vulnerable to progressive brittle punching shear failure under seismic action. In the present work performance of flat slab under lateral loading has been studied using pushover analysis. Shear wall was added to the bare frame to analyze the performance of the dual system. Addition of shear wall was found to improve the performance and the system could be used for lateral loads also. Yield pattern shows that flat slab building behaves as strong column- weak beam system. As the percentage of shear wall increases, drift ratio decreases and location of maximum drift ratio also shifts to upper stories, which indicates that shear wall governs the behavior of the system under lateral loads.